Ethanol production from alkali-pretreated oil palm empty fruit bunch by simultaneous saccharification and fermentation with mucor indicus. Issue 6 (2nd May 2016) - Christia, Abdi; Setiowati, Arima Diah; Millati, Ria; Karimi, Keikhosro; Cahyanto, Muhammad Nur; Niklasson, Claes; Taherzadeh, Mohammad J.
ABSTRACT: Oil palm empty fruit bunch (OPEFB) is a potential raw material for production of lignocellulosic bioethanol. The OPEFB was pretreated with 8% sodium hydroxide (NaOH) solution at 100°C for 10 to 90 min. Enzymatic digestion was carried out using cellulase and β-glucosidase at 45°C for 24 h. It was then inoculated with Mucor indicus spores suspension and fermented under anaerobic conditions at 37°C for 96 h. Sodium hydroxide pretreatment effectively removed 51–57% of lignin in the OPEFB and also its hemicellulose (40–84%). The highest glucan digestibility (0.75 g/g theoretical glucose) was achieved in 40-min NaOH pretreatment. Fermentation by M. indicus resulted in 68.4% of the theoretical ethanol yield, while glycerol (16.2–83.2 mg/g), succinic acid (0–0.4 mg/g), and acetic acid (0–0.9 mg/g) were its by-products. According to these results, 11.75 million tons of dry OPEFB in Indonesia can be converted into 1.5 billion liters of ethanol per year.